Contracultura TV: segmento “Bonus Track” - Villavicencio Richter, Max Oskar (2020)
The following professional work seeks to produce a documentary segment belonging to the digital channel “ContraCultura TV” called “Bonus Track” that deals with topics related to music, art and entertainment of the local scene, in order to disseminate musical and informative content unconventional of new Peruvian musical talents and generate a space for interaction between followers and them. After conceptualizing the format, pre-producing, producing and post-producing it, its function is sought at the level of general interest and it is subjected to validation by the target audience, interviews with specialists in the audiovisual and journalistic field and finally, after making adjustments in the content at the level of length and dynamism, to evaluative tests with a final version. As a result, lessons were obtained that served to improve the following episodes of the segment and its effectiveness